Do acesso à justiça e da duração razoável do processo no âmbito prioritário de tramitação de pessoas idosas: análise de processos autuados em 2019 nas varas cíveis da comarca de Palmas/TO - Pinto, Bruna Patrícia Ferreira (Universidade Federal do Tocantins, 2021)
The present work is a conclusive technical report linked to the research line Instruments of Jurisdiction, Access to Justice and Human Rights, sub-area Access to Justice and Protection of Rights, of the Stricto Sensu Graduate Program Professional and Interdisciplinary Master in Jurisdictional Provision and Human Rights (MPPJDH), of the Federal University of Tocantins (UFT), in partnership with the Superior School of the Judges of the State of Tocantins (ESMAT) has as object of study, the constitutional principles of fundamental rights of the guaranteed access to justice and reasonable duration of the process with an emphasis on the priority right to procedural processing of the elderly in the Civil Courts of the City of Palmas in 2019. It is composed of theoretical part and data analysis with descriptive-exploratory research and quantiqualitative approach, through technical, documentary and bibliographic procedure, with an empirical focus, which aims to understand the problem presented. As it is of an applied nature, in addition to the construction of the diagnosis, the collected results made it possible to indicate suggestions and propositions, which if accepted may direct the implementation of actions aimed at the realization of the object of study under consideration, with a view to improving the provision of jurisdiction to ensure and guarantee in its fullness, the rights of the elderly with real benefits for society as a whole.